(untitled) (Bangabandhu Sheikh Mujib Medical College Journal, 2024)
Preterm birth is a leading cause of infant morbidity and death. And the ideal mode of delivery for preterm gestations is still debated. Studies suggest that Caesarean section is associated with improved neonatal outcomes for groups of mothers or infants with major comorbidities. With the aim to study the indication and outcome of Caesarean section in preterm pregnancy in Bangladesh, this cross-sectional descriptive study was conducted at Bangabandhu Sheikh Mujib Medical College Hospital, Faridpur from July 2022 to December 2022 on a total of 82 cases. Among them, 15(18.29%) had preterm labour with previous LUCS ē scar tenderness, followed by 13(15.85%) placenta previa, 11(13.41%) PROM, 10(12.20%) abruptio placenta, 10(12.20%) preterm labour pain with fetal distress, 10(12.20%) eclampsia, 7(8.54%) severe preeclampsia and 2(3.13%) malpresentation with cord prolapse. 42(51.22%) gave birth to an alive healthy baby. Most of the babies weighted 2.1-2.4kg for 28 (34.15%), followed by 1.6-2 kg for 17 (20.73%). 42(51.22%) babies did not need to admit in SCANU. 35 (42.68%) neonates had no complications, whereas others had PNA, RDS, TTN,hyperbilirubinemia, IUGR etc. A clear understanding of the outcomes of caesarean section in preterm pregnancy and the indications for the procedures might assist in making the best decisions. Bangabandhu Sheikh Mujib Med. Coll. J. 2024;3(2):79-84